Evaluasi Kinerja Jabatan Fungsional Tenaga Kependidikan di Universitas Negeri Surabaya - Reni Dwi Jayanti; Suprapto; Sarmini; Sugeng Harianto; Sulistyorini (Department of Public Administration, Universitas Negeri Surabaya, 2022)
The purpose of this study was to evaluate the performance of the functional positions of education personnel at the State University of Surabaya (Unesa). This study focuses on evaluating the performance of the functional positions of Unesa education staff which includes the input dimensions, process dimensions and output dimensions as well as various data needed for structuring and developing the careers of education personnel towards PTNBH. Data was collected through workshops and Focus Group Discussions (FGD), as well as questionnaires. The data analysis technique required is statistical technique with percentages. The results of this study show several things, namely: (1) The Staffing Section of Unesa does not yet have a job description document in accordance with applicable laws and regulations; (2) This study develops 79 instruments detailing certain functional and functional position tasks of general Unesa education personnel; (3) Understanding of the subject in the input dimension in good and excellent condition; (4) The results of mapping in the dimensions of the process and the dimensions of the product are obtained the result that the general functional is better than the particular functional; (5) In general, the general functional education personnel does not have a professional organization and relatively few of them have participated in workshops or training. Later on, the Institution provides opportunities for education personnel to increase capacity and competence in accordance with their functional positions.